Emerging Technologies for Education: 6th International Symposium, SETE 2021, Zhuhai, China, November 11-12, 2021, Revised Selected Papers - Jia, Weijia; Tang, Yong; Lee, Raymond S. T; Herzog, Michael; Zhang, Hui; Hao, Tianyong; Wang, Tian (Lecture Notes in Computer Science, 2022)
This book constitutes the refereed conference proceedings of the 6th International Symposium on Emerging Technologies for Education, SETE 2021, held in Zhuhai, China in November 2021.35 full papers were accepted together with 8 short papers out of 58 submissions. The papers focus on the following subjects:  Emerging Technologies for Education, Digital Technology, Creativity, and Education; Education Technology (Edtech) and ICT for Education; Education + AI; Adaptive Learning, Emotion and Behaviour Recognition and Understanding in Education; as well as papers from the International Symposium on User Modeling and Language Learning (UMLL2021) and the International Workshop on Educational Technology for Language Learning (ETLL 2021).